2019
DOI: 10.1021/acs.organomet.9b00545
|View full text |Cite
|
Sign up to set email alerts
|

Olefin Insertion Reactivity of a (Phosphine-arenesulfonate)Palladium(II) Fluoride Complex

Abstract: The synthesis of the phosphine-arenesulfonate Pd­(II) fluoride complex (PO-OMe)­PdF­(lut) (2, PO-OMe = P­(2-OMe-Ph)2(2-SO3-5-Me-Ph), lut = 2,6-lutidine) and its reactions with electron-deficient olefins are described. The reaction of (PO-OMe)­PdBr­(lut) (1) with AgF affords 2 as an 82:18 mixture of cis-P,F and trans-P,F isomers. 2 isomerizes to a 1:2 cis-P,F:trans-P,F equilibrium mixture in CD2Cl2 solution at room temperature in ca. 3 days. 2 reacts with vinyl fluoride (VF) to afford (PO-OMe)­Pd­(CH2CHF2)­(lut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…The ethylene/VF copolymers produced by C in hexanes exhibit broad MWDs (Table 1, entries 3,4; Figure 2). Given the nearly ideal single-site behavior observed in ethylene homopolymerization tral cage, leading to the formation of new active Pd species [23,25,[48][49][50][51][52]. Consistent wit sal, -CH2CH2F and -CH2CHF2 end groups, which are formed by ethylene and VF inserti pecies in copolymerization by mononuclear catalysts A, are not observed in the copol ced by C (Figure 3) [23].…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The ethylene/VF copolymers produced by C in hexanes exhibit broad MWDs (Table 1, entries 3,4; Figure 2). Given the nearly ideal single-site behavior observed in ethylene homopolymerization tral cage, leading to the formation of new active Pd species [23,25,[48][49][50][51][52]. Consistent wit sal, -CH2CH2F and -CH2CHF2 end groups, which are formed by ethylene and VF inserti pecies in copolymerization by mononuclear catalysts A, are not observed in the copol ced by C (Figure 3) [23].…”
Section: Resultsmentioning
confidence: 94%
“…Given the nearly ideal single-site behavior observed in ethylene homopolymerization by C in hexanes, it is unlikely that the broadening of the MWD of the ethylene/VF copolymers formed in this solvent is due to thermal disassembly of the cage structure (Figure 2). One possibility is that nucleophilic Pd-F species generated by 1,2-VF insertion and β-F elimination react with the Li + ions in the central cage, leading to the formation of new active Pd species [23,25,[48][49][50][51][52]. Consistent with this proposal, -CH 2 CH 2 F and -CH 2 CHF 2 end groups, which are formed by ethylene and VF insertion of Pd-F species in copolymerization by mononuclear catalysts A, are not observed in the copolymer produced by C (Figure 3) [23].…”
Section: Clusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Jordan and co-workers demonstrated that fluoroolefins can be inserted into the Pd-F bond to form fluoroalkylpalladium species. Beyond the detailed mechanistic studies of this elementary step including DFT studies, 45 this insertion step enabled the copolymerization of ethylene and fluoroolefins to generate polyethylene that contained a fluoromethyl chain end. 46 The transition-metal-mediated C-F bond activation also enables the selective transformation of fluoroalkenyl species to hydrofluorocarbons.…”
Section: Short Review Synthesismentioning
confidence: 99%